Modeling the spatial variability in the spread and correlation of childhood malnutrition in Nigeria. (15th January 2019) - Gayawan, Ezra; Adebayo, Samson B.; Waldmann, Elisabeth
Abstract : The average nutritional status of children in Nigeria is, just as in most developing countries, still in an alarmingly bad condition. Prior studies have shown that this status relies on a series of different influences and can be measured by three anthropometric variables for stunting, wasting, and underweight. Different regression modeling techniques have been adopted over the years to explain the determinants and spatial clustering. Those indicators, however, show patterns that are not necessarily full filling requirements for ordinary regression models for the mean and are correlated among each other, a fact that has until now been ignored by most studies. Methods to model outcomes in the light of both, the whole distribution of and the correlation between two or more outcomes based on a set of covariates, have lately been developed. The aim of this paper is to make use of those methods to explain the underlying spatial structure in malnutrition in Nigeria. The study brings to limelight the pattern of spread as well as the interwoven relationships among childhood malnutrition indicators that would have otherwise remained unknown in Nigeria.